Pressure-induced maturation of endothelial cells on newborn mouse carotid arteries - Flavahan, Sheila (American Physiological Society, 2013)
Experiments investigated maturation of endothelial function in the postnatal period. Carotid arteries isolated from newborn (postnatal day 1, P1) to P21 mice were assessed in myographs at transmural pressure (P(TM)) of 20 mmHg (P1 blood pressure, BP). Acetylcholine was ineffective in P1 but powerfully dilated P7 arteries, whereas NO-donor DEA-NONOate caused similar dilation at P1 and P7. Dilation to acetylcholine at P7 was abolished by inhibition of NO synthase (NOS) (l-NAME) or of phosphoinositide-3-kinase (PI3K) (wortmannin, LY294002). Endothelial NOS (eNOS) expression decreased in P7 compared with P1 arteries, although acetylcholine increased PO(4)-eNOS-Ser(1177) in P7 but not in P1 arteries. Endothelial maturation may therefore reflect increased signaling through PI3K, Akt, and eNOS. Systemic BP increases dramatically in the early postnatal period. After exposing P1 arteries to transient increased P(TM) (50 mmHg, 60 min), acetylcholine caused powerful dilation and increased PO(4)-eNOS-Ser(1177). Pressure-induced rescue of acetylcholine dilation was abolished by PI3K or NOS inhibition. Transient increased P(TM) did not affect dilation at P7, or dilation to NO-donor in P1 arteries. Width of endothelial adherens junctions (VE-cadherin immunofluorescence) increased significantly from P1 to P7, and in P1 arteries exposed to transient increased P(TM). A function-blocking antibody to VE-cadherin reduced the pressure-induced rescue of acetylcholine responses at P1, and the dilation to acetylcholine in P7 arteries. Therefore, maturation of newborn endothelium dilator function may be induced by increasing BP in the postnatal period. Furthermore, this may be mediated by VE-cadherin signaling at adherens junctions. Interruption of this maturation pathway may contribute to developmental and adult vascular diseases.